Integrative policy development for agricultural priority areas: Balancing land suitability and commodity preferences - Putri, Nadya Paramitha; Frimawaty, Evi; Wibowo, Adi (Holistic: Journal of Tropical Agriculture Sciences, 2025)
Background: Indonesia has the potential of natural resources to support agriculture. However, there are still some areas that have not optimized natural resources. People focus on planting commodity crops without considering the physical conditions of the environment and socio-culture. This research aims to develop policy directions for agricultural priority areas that consider the physical conditions of the environment and their suitability for farmers' commodity preferences. Methods: This study uses a quantitative approach with a combined method to determine agricultural priority areas. It integrates ZAE analysis, land carrying capacity, and farmers' commodity preferences. Findings: The results showed that the commodities preferred by farmers were cocoa, corn, and upland rice. The preference for these commodities has a significant correlation, especially with the source of income and the size of cultivated land. There is a 51% mismatch of existing agricultural land with the ZAE while in general agriculture in Nangapanda is in accordance with the carrying capacity of the land because it is at a high level of carrying capacity. Conclusion: Based on the agricultural priority areas formed, agriculture in Nangapanda can utilize dry land mainly for plantations with the direction of the main commodities tailored to the physical conditions of the land and the preferences of farmers namely cocoa, cashew, cloves, nutmeg, pepper. Novelty/Originality of this article: The novelty of this research lies in the integrative approach in formulating agricultural priority area policies that combine the suitability of physical environmental conditions and farmers' commodity preferences, which has not been widely applied in similar studies.